(untitled) (Environment & Health, 2022)
Objective: We generalized and assessed the prior chemical pollutants in accordance with the time of their averaging by the data of domestic and foreign regulatory frameworks. Materials and methods: To achieve the goal, we used the bibliographic and analytical methods. We analyzed the databases of Ukraine and the EU countries, the USA and Canada on the current standards for chemical agents and the time of their averaging in accordance with the purpose - prevention of acute and chronic effects. Results and discussion: As a result of the comparison of the data on the regulations and standards for chemical agents in ambient air, we identified the agents that are criterial ones in most countires. For these substances, monitoring methods have been developed and standards have been substantiated and adopted for two averaging periods: twenty-minute and average daily. In most countries, two standards have been also adopted for each agent, but the averaging period is longer there: an average annual and a daily average. Such standards may control and prevent the chronic effect of substances. As a result, the use of the Ukrainian and foreign standards leads to the controversial estimates of the actual air pollution. The average daily standard adopted in Ukraine, on the one hand, is much stricter in comparison with the similar foreign criteria, and on the other hand, it does not correspond to the peculiarities of the formation of ambient air pollution, and is inadequate for the averaging time. Conclusions: 1. Comparative analysis of hygienic standards indicates the needs to harmonize the ambient air quality standards in force in Ukraine with international ones. 2. The existing system of the hygienic standards in Ukraine must be supplemented with the standard for the annual averaging period by transferring the operating average daily concentrations to this rank.